Ductile fracture of a metal matrix composite studied using 3D numerical modeling of void nucleation and coalescence. (15th February 2018) - Shakoor, Modesar; Bernacki, Marc; Bouchard, Pierre-Olivier
Highlights: Ductile fracture's particle debonding and fragmentation mechanisms modeled in full 3D. Finite element analysis of large and random arrangements of particles. Parallel mesh adaption tools to conduct simulations at large plastic strain. Results revealing an interaction mechanism between void nucleation and coalescence. Comparison with conventional approaches showing a major influence on ductility. Abstract: A finite element analysis of large 3D microstructures of randomly distributed particles is proposed to investigate the influence of particle debonding and fragmentation on void coalescence. This analysis is possible thanks to recent developments in parallel automatic remeshing techniques tailored for simulations of microstructures undergoing large deformations. These techniques are extended herein to model void nucleation by particle debonding and fragmentation. Micromechanical simulations of a model material with 20% particle volume fraction show that void nucleation leads to an early plastic strain localization micromechanism that favors void coalescence and reduces ductility significantly.